Reducing cytogenetic testing in the era of next generation sequencing: Are we choosing wisely?. (29th October 2021) - Kawata, Eri; Hedley, Benjamin D.; Chin‐Yee, Benjamin; Xenocostas, Anargyros; Lazo‐Langner, Alejandro; Hsia, Cyrus C.; Howson‐Jan, Kang; Yang, Ping; Levy, Michael A.; Santos, Stephanie; Bhai, Pratibha; Howlett, Christopher; et al.
Abstract: Introduction: In most laboratories, next generation sequencing (NGS) has been added without consideration for redundancy compared to conventional cytogenetics (CG). We tested a streamlined approach to genomic testing in patients with suspected myeloid and plasma cell neoplasms using next generation sequencing ("NGS first") as the primary testing modality and limiting cytogenetics (CG) to samples with morphologic abnormalities in the marrow aspirate. Methods: Based on morphologic interpretation of bone marrow aspirate and flow cytometry, samples were triaged into four groups: (a) Samples with dysplasia or excess blasts had both NGS and karyotyping; (b) Samples without excess blasts or dysplasia had NGS only; (c) Repeat samples with previous NGS and/or CG studies were not retested; (d) Samples for suspected myeloma with less than 5% plasma cell had CG testing cancelled. Results: Seven hundred eleven adult bone marrow (BM) samples met the study criteria. The NGS first algorithm eliminated CG testing in 229/303 (75.6%) of patients, primarily by reducing repeat testing. Potential cost avoided was approximately 124 000 per annum. Hematologists overruled the triage comment in only 11/303 (3.6%) cases requesting CG testing for a specific indication. Conclusions: Utilizing NGS as the primary genomic testing modality NGS was feasible and well accepted, reducing over three quarters of all CG requests and improving the financial case for adoption of NGS. Key factors for the success of this study were collaboration of clinical and genomic diagnostic teams in developing the algorithm, rapid turnaround time for BM interpretation for triage, and communication between laboratories.